1999
DOI: 10.1002/(sici)1097-4679(199905)55:5<553::aid-jclp3>3.3.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Portuguese version of the beck depression inventory on Brazilian college students

Abstract: The psychometric properties of the Portuguese version of the Beck Depression Inventory were studied on a large Brazilian college student sample (N = 1,080; 845 women, 235 men). The BDI scores according to sociodemographic characteristics and mean individual item scores for total sample and by gender were compared. BDI scores tend to be higher for women, for those who work, and for the younger participants. The reliability of the inventory estimated by alpha coefficient was high for the total sample (.86) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(22 citation statements)
references
References 15 publications
2
19
0
1
Order By: Relevance
“…It is a 21-item questionnaire, with a 4-point Likert scale. It was already available in a Portuguese translation, which has recently been found to possess good psychometric properties (Gorenstein, Andrade, Viera Filho, Tung, & Artes, 1999). Six hundred and six participants produced valid BDI data.…”
Section: Methodsmentioning
confidence: 99%
“…It is a 21-item questionnaire, with a 4-point Likert scale. It was already available in a Portuguese translation, which has recently been found to possess good psychometric properties (Gorenstein, Andrade, Viera Filho, Tung, & Artes, 1999). Six hundred and six participants produced valid BDI data.…”
Section: Methodsmentioning
confidence: 99%
“…The McGill pain questionnaire 26,27 and the Beck depression inventory 28,29 were also used as psychometric instruments. The McGill pain questionnaire 26,27 and the Beck depression inventory 28,29 were also used as psychometric instruments.…”
Section: Methodsmentioning
confidence: 99%
“…This yielded a correlation of .60 ( p <.001) for Time 1 and .64 ( p <.001) for Time 2, further indicating the utility in evaluation of depression symptomatology. Finally, another Brazilian study concluded that the SRQ‐20 was particularly effective at evaluating depression (Gorenstein, Andrade, Filho, Tung, & Artes, 1999). Based on these results, the SRQ‐20 was considered to be a valid measure of depression symptomatology.…”
Section: Methodsmentioning
confidence: 99%